1979
DOI: 10.1099/00221287-114-1-201
|View full text |Cite
|
Sign up to set email alerts
|

Nigericin-induced Death of an Acidophilic Bacterium

Abstract: 201At an external pH of 3.5, nigericin (which catalyses an electroneutral H+/K+ exchange) abolished the transmembrane proton gradient (ApH) of Bacillus acidocaldarius, causing a rapid acidification of the cytoplasm from approximately pH 6.0 to pH 3.5. A pronounced loss of viability and fine-structural changes rapidly followed treatment with nigericin. A marked decline in respiration and an even more rapid decrease in cytoplasmic ATP were observed. Activity of at least one cytoplasmic enzyme decreased more slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Initial studies on a range of acidophiles suggested that uncouplers and inhibitors of respiration did not cause the complete dissipation of the pH gradient (67,73). However, transport of solutes via H+-linked systems was inhibited (39). The maintenance of ApH in the presence of uncouplers has been attributed to either limited cation permeability across the membranes of acidophiles or high cytoplasmic buffering capacity in the cells (126,127).…”
Section: Acidophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies on a range of acidophiles suggested that uncouplers and inhibitors of respiration did not cause the complete dissipation of the pH gradient (67,73). However, transport of solutes via H+-linked systems was inhibited (39). The maintenance of ApH in the presence of uncouplers has been attributed to either limited cation permeability across the membranes of acidophiles or high cytoplasmic buffering capacity in the cells (126,127).…”
Section: Acidophilesmentioning
confidence: 99%
“…If these cations were to be exchanged for H+, this would result in the buffering capacity being outstripped. Indeed, there is evidence that, when K+-H+ exchange is stimulated by the addition of nigericin at acid pH, acidification of the cytoplasm occurs to an extent that causes denaturation of the proteins (39). Thus the intrinsic cation impermeability of the membrane of acidophiles may be important in protection against excessive acidification.…”
Section: Acidophilesmentioning
confidence: 99%
“…Cells treated with 2,4-dinitrophenol were used as a control to determine the extent of nonspecific binding of aspirin, and the extent of this nonspecific binding was not stated (72). It is, however, clear that the action of either uncouplers or the antibiotic nigericin (which catalyzes H+/Na+ or H+/K+ exchange) can result in a collapse of ApH of sufficient magnitude to cause disorganization of cell contents and complete loss of cell viability (45). Oshima et al (105) have also measured l\pH in B. acidocaldarius, but since they used DMO as a probe their data are open to question.…”
Section: Ai1h+ In Acidophilic Heterotrophsmentioning
confidence: 99%
“…Acidification of the pH;n in the absence of K+ or Rb+ implies that these cations have roles in pHin regulation at neutral pH (see Table 1). It has been reported that the acidification of pHin inhibits the growth of E. coli (2) and other bacteria (5). But in obligatory alkalophilic bacteria the explanation for the failure to grow at neutral pH is not the excessive acidification of the pHin but an inadequate ability of the respiratory chain to generate a dfH at neutral pH (2,9,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%